2001
DOI: 10.1111/1469-7610.00767
|View full text |Cite
|
Sign up to set email alerts
|

Annotation: The Cognitive Neuroscience of Face Recognition: Implications for Developmental Disorders

Abstract: Face recognition is often considered to be a modular (encapsulated) function. This annotation supports the proposal that faces are special, but suggests that their identification makes use of general-purpose cortical systems that are implicated in high-level vision and also in memory and learning more generally. These systems can be considered to function within two distinct cortical streams: a medial stream (for learning and salience of faces encountered) and a lateral stream (for distributed representations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 106 publications
(120 reference statements)
1
39
0
Order By: Relevance
“…12,13 On the other hand, others argue that, even without a primary perceptual deficit, the presence of an SDD may impair the acquisition of normal face expertise during childhood. [14][15][16][17] Since the ability to discriminate subtle differences between faces develops during childhood and requires exposure and interest, 18 the development of this perceptual skill may be hampered by a social apathy that may extend to the avoidance of looking at faces. 19,20 A number of studies have documented difficulties with recognition of known faces 21 and new faces 22 and abnormal face-induced responses in event-related potentials 23 and magnetoencephalography.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 On the other hand, others argue that, even without a primary perceptual deficit, the presence of an SDD may impair the acquisition of normal face expertise during childhood. [14][15][16][17] Since the ability to discriminate subtle differences between faces develops during childhood and requires exposure and interest, 18 the development of this perceptual skill may be hampered by a social apathy that may extend to the avoidance of looking at faces. 19,20 A number of studies have documented difficulties with recognition of known faces 21 and new faces 22 and abnormal face-induced responses in event-related potentials 23 and magnetoencephalography.…”
Section: Discussionmentioning
confidence: 99%
“…As we have discussed earlier in this chapter, research on face processing and brain activity in typical individuals has concluded that there is a specific area in the brain that is activated when individuals are presented with face stimuli (Farah, 1996;Elgar & Campbell, 2001;Halit et al, 2004). It is well established that when hemispheric asymmetry for face processing is observed, the right rather than the left hemisphere is implicated in face processing, and specifically the middle part of the right fusiform gyrus shows activation and has been named 'Fusiform Face Area' (FFA) (Elgar & Campbell, 2001) (See Chapter 2 for details).…”
Section: Neuropsychological Studies Of Face Processing In Asdmentioning
confidence: 92%
“…Where hemispheric asymmetry occurs, the right rather than the left hemisphere is implicated in face processing. The middle part of the right fusiform gyrus shows activation in all reported studies and has been named the 'Fusiform Face Area' (FFA) (Elgar & Campbell, 2001). Also, behavioural studies using unilateral presentation of face images generally demonstrated a right hemisphere (left visual field) superiority in face recognition.…”
Section: Face Processing and Brain Activitymentioning
confidence: 99%
See 2 more Smart Citations